2022
DOI: 10.1002/essoar.10511211.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High carbon mineralization rates in subseafloor hadal sediments - Result of frequent mass wasting

Abstract: Only recently it has been realized that hadal trenches harbor a surprisingly high biological activity (Bartlett, 2009;Danovaro et al., 2003;Jamieson, 2015). In situ measurements have documented that microbial oxygen depletion at the seafloor surface in deep sea trenches is far more efficient than would be expected at such great water depths (Glud et al., 2013;Luo et al., 2018;Wenzhöfer et al., 2016). These findings suggest that the input of degradable material must be considerably greater than estimated assumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
3
4
0
2
Order By: Relevance
“…These assessments demonstrate that despite highly elevated microbial mineralization, hadal regions accumulate relatively large amounts of organic material. The current findings align with other recent investigations that demonstrating the importance of tectonic induced mass wasting for translocating organic carbon to the hadal environment (Bao et al., 2018; Kioka et al., 2019b; Zabel et al., 2022) and previous indirect evidence arguing for high carbon accumulation in hadal sediments (Luo et al., 2017; Xu et al., 2021), as well as recent findings of highly elevated sequestration of black carbon in some hadal settings (Zhang et al., 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These assessments demonstrate that despite highly elevated microbial mineralization, hadal regions accumulate relatively large amounts of organic material. The current findings align with other recent investigations that demonstrating the importance of tectonic induced mass wasting for translocating organic carbon to the hadal environment (Bao et al., 2018; Kioka et al., 2019b; Zabel et al., 2022) and previous indirect evidence arguing for high carbon accumulation in hadal sediments (Luo et al., 2017; Xu et al., 2021), as well as recent findings of highly elevated sequestration of black carbon in some hadal settings (Zhang et al., 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our assessments also suggest that trenches are characterized by continuous accumulation of material focusing, even during periods without mass wasting (Figure 4b). Both the continuous and the erratic enhancement of material deposition might have important implications for the balance between microbial mineralization and burial of organic material and thereby long‐term carbon sequestration in trench regions and the deep sea in general (Zabel et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous studies in the Japan and Atacama Trenches (Nakatsuka et al, 1997;. However, deeply buried sediment from the Atacama Trench has revealed phases of slow pelagic sedimentation in the past that alternate with rapid mass-wasting events, which fuel microbial carbon turnover at remarkably high rates Zabel et al, 2022). Thus, we expect that the recycling by piezophilic bacteria in the hadal region of organic matter originated from primary production in the surface ocean and the downslope transport will alter the isotopic composition of sedimentary carbon and nitrogen (Xu et al, 2018 and references therein).…”
Section: Organic Matter Provenancesupporting
confidence: 92%
“…However, high remineralization due to intense heterotrophic activity has also been demonstrated in the Atacama Trench , Glud et al, 2021. Therefore, although previous studies have suggested an important contribution of OM from material accumulated in sediments on the continental shelf, to hadal benthic zone (Flores et al, 2022;Oguri et al, 2022;Zabel et al, 2022), the contribution of OM from the euphotic zone to hadalpelagic zone could be more than expected.…”
Section: What Is the Relative Contribution Of Allochthonous Sources T...mentioning
confidence: 94%